Clinical Characteristics and Long-Term Outcomes of Patients With Differing Haemoglobin Levels Undergoing Semi-Urgent and Elective Percutaneous Coronary Intervention in an Asian Population - Soh, Rodney Yu-Hang; Sia, Ching-Hui; Djohan, Andie Hartanto; Lau, Rui-Huai; Ho, Pei-Ying; Neo, Jonathan Wen-Hui; Ho, Jamie Sin-Ying; Sim, Hui-Wen; Yeo, Tiong-Cheng; Tan, Huay-Cheem; Chan, Mark Yan-Yee; Loh, Joshua Ping-Yun (Frontiers in Cardiovascular Medicine, 2022)
IIntroduction This study aimed to investigate impact of anaemia on long-term clinical outcomes of patients who underwent semi-urgent and elective percutaneous coronary intervention (PCI) in an Asian population. Although the effects of anaemia on outcomes in Asian patients are well studied for acute coronary syndrome, its impact on Asian patients undergoing semi-urgent and elective PCI are unclear. Methods This was a retrospective cohort study of patients who underwent semi-urgent and elective PCI from January 1, 2014 to December 31, 2015 at a tertiary academic centre. 1685 patients were included. They were stratified into 3 groups – normal (12g/dL), intermediate (10-11.9g/dL) and low (<10g/dL) haemoglobin levels. Demographics, risk factors and end-points including 5-point major adverse cardiac and cerebrovascular events (MACCE) (all-cause death, subsequent stroke, myocardial infarction and congestive cardiac failure, target lesion revascularisation), cardiovascular death, and bleeding events were analysed. Results Patients in intermediate and low haemoglobin level groups were older with more co-morbidities. Compared to normal haemoglobin level group, low haemoglobin level group patients were associated with increased risk of composite endpoints of all-cause death, subsequent stroke, myocardial infarction, congestive cardiac failure and target lesion revascularisation (adjusted hazard ratio (aHR) 1.89, 95% confidence interval (CI):1.22, 2.92; p=0.004). This was driven by the increased risk of target lesions revascularization observed in low haemoglobin level group compared to normal haemoglobin level group (aHR 17.74, 95% CI: 1.74, 180.80; p=0.015). The patients in the low haemoglobin level group were also associated with higher risk of bleeding events, compared to normal haemoglobin level group (aHR 7.18, 95% CI: 1.13, 45.40; p=0.036). Conclusion In our Asian cohort, anaemic patients undergoing PCI were associated with higher co-morbid burden. Despite adjustments for co-morbidities, these patients had higher mortality and worse cardiovascular outcomes following contemporary PCI.